Oral cavity and oropharyngeal squamous cell carcinoma—an update. (27th July 2015) - Chi, Angela C.; Day, Terry A.; Neville, Brad W.
<x xml:space="preserve">Abstract</x> Answer questions and earn CME/CNE Oral cavity squamous cell carcinoma (OC‐SCC) is the most common malignancy of the head and neck (excluding nonmelanoma skin cancer). Recent trends have shown a dramatic rise in the incidence of oropharyngeal squamous cell carcinoma (OP‐SCC), with a marked increase in lesions related to human papillomavirus infection. This update presents the latest evidence regarding OC‐SCC and OP‐SCC. In particular, the authors compare and contrast tumors at these two sites with respect to epidemiology, etiopathogenesis, clinicopathologic presentation, clinical assessment, imaging, management, and prognosis. It is important for clinicians to be aware of differences between OC‐SCC and OP‐SCC so that appropriate patient education and multidisciplinary care can be provided to optimize outcomes. CA Cancer J Clin 2015;65:401–421. © 2015 American Cancer Society.